PERANCANGAN PROSES SISTEM PAINTING DI PERUSAHAAN OTMOTIF MENGGUNAKAN SOFTWARE “STARUML” - Jihan Fadhilah Lukman; Muhammad Dimas Ramadhan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Information Systems are important components that help businesses operate better and more efficiently. As part of the agricultural sector, tea companies need an integrated information system to better manage the production process. The use of software such as StarUML becomes relevant in this case. StarUML is a tool that can be used to design various models for software development, such as use case diagrams, class diagrams, and activity diagrams. Its ability to facilitate system design from multiple points of view, from the business process level to technical implementation, is a key advantage of StarUML. Its ability to facilitate system design from multiple points of view, from the business process level to technical implementation, is a key advantage of StarUML. Actors, such as system users, and how they interact with the system can be identified using use case diagrams. In this case, the main actors involved in the use of the painting process information system can be identified as painting operators, painting process managers, and Quality Control (QC).